2021
DOI: 10.1111/irv.12904
|View full text |Cite
|
Sign up to set email alerts
|

Lower cognitive scores among toddlers in birth cohorts with acute respiratory illnesses, fevers, and laboratory‐confirmed influenza

Abstract: Background: We established cohorts to assess associations between viral influenza and cognitive development to inform the value proposition of vaccination. Methods: From 2014 through 2017, we called women seeking care at four prenatal clinics in Panama and El Salvador to identify acute respiratory illnesses (ARIs). Within 2 weeks of childbirth, mothers were asked to enroll their neonates in the cognitive development study. Staff obtained nasopharyngeal swabs from children with febrile ARIs for real-time revers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Accumulating data from multinational cohorts suggest that neurodevelopment may have a related, but distinct causal pathway from stunting. 9,[30][31][32][33]36,37 Indeed, the aforementioned Bangladeshi cohort found that birth anthropometry and maternal weight were better predictors of growth, while clinical (fever) and biological markers of inflammation were more strongly associated with neurodevelopment. [5][6][7]9 Though not completely analogous to recurrent infections, mounting evidence suggests that human immunodeficiency virus (HIV)-infected, or even HIV-exposed, uninfected infants and children demonstrate neurodevelopment delays likely attributable to inflammation and immune dysregulation.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating data from multinational cohorts suggest that neurodevelopment may have a related, but distinct causal pathway from stunting. 9,[30][31][32][33]36,37 Indeed, the aforementioned Bangladeshi cohort found that birth anthropometry and maternal weight were better predictors of growth, while clinical (fever) and biological markers of inflammation were more strongly associated with neurodevelopment. [5][6][7]9 Though not completely analogous to recurrent infections, mounting evidence suggests that human immunodeficiency virus (HIV)-infected, or even HIV-exposed, uninfected infants and children demonstrate neurodevelopment delays likely attributable to inflammation and immune dysregulation.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating data from multinational cohorts suggest that neurodevelopment may have a related, but distinct causal pathway from stunting. 9, 25-28, 31, 32 Indeed, the aforementioned Bangladeshi cohort found that birth anthropometry and maternal weight were better predictors of growth, while clinical (fever) and biological markers of inflammation were more strongly associated with neurodevelopment. 5-7, 9 Though not completely analogous to recurrent infections, mounting evidence suggests that human immunodeficiency virus (HIV)-infected, or even HIV-exposed, uninfected infants and children demonstrate neurodevelopment delays likely attributable to inflammation and immune dysregulation.…”
Section: Discussionmentioning
confidence: 99%
“…When certain conditions are present, there is a link between certain infectious diseases, such as viral encephalitis, and cognitive deficits. 22 Children aged 12 months with acute respiratory illnesses (ARI) and fever had lower cognitive scores, according to the findings of a study conducted by Azziz-Baumgartner et al 23 It is possible, but not certain, that this finding was related to increased levels of pro-inflammatory interleukin during illness. 23 In addition to enteric infections and malnutrition in the first two years of life, enteric infections and malnutrition are linked to later cognitive impairment.…”
Section: Evidence On the Impact Of Abnormal Immune System And Cogniti...mentioning
confidence: 95%
“…22 Children aged 12 months with acute respiratory illnesses (ARI) and fever had lower cognitive scores, according to the findings of a study conducted by Azziz-Baumgartner et al 23 It is possible, but not certain, that this finding was related to increased levels of pro-inflammatory interleukin during illness. 23 In addition to enteric infections and malnutrition in the first two years of life, enteric infections and malnutrition are linked to later cognitive impairment. A study evaluated the long-term effects of childhood diarrhea in the first two years of life by examining the cognitive function of Brazilian slum children.…”
Section: Evidence On the Impact Of Abnormal Immune System And Cogniti...mentioning
confidence: 95%
See 1 more Smart Citation